Financial Literacy among Banking Product/Service Users of Nepal: A Bibliometric Analysis of Scientific Research Papers - Neupane, Sangam (NPRC Journal of Multidisciplinary Research, 2026)
Background: Financial literacy is a key driver of effective participation in formal banking systems and sustainable financial inclusion. In Nepal, the rapid expansion of banking and digital financial services has heightened the need to understand the associated research landscape, yet a consolidated scholarly assessment remains limited.Objectives: This study aims to systematically examine the status, growth, and thematic focus of scientific research on financial literacy among banking product and service users in Nepal through a bibliometric analysis.Methods: A bibliometric analysis was conducted on 161 peer-reviewed articles indexed in Dimensions.ai (2016–2025). The methodology included descriptive performance analysis and network visualization using VOSviewer to assess publication trends, citation patterns, leading contributors, and keyword co-occurrence.Findings: Results indicate a steep rise in publications and citations post-2023, with Nepal as the dominant contributor, led by institutions like Tribhuvan University. Thematic analysis reveals a focus on financial literacy, investment behavior, and financial inclusion, aligned with Sustainable Development Goals. Key gaps include a lack of empirical, product-specific, and digital financial literacy studies.Conclusion: While research output and impact are growing, the field requires a strategic shift towards more empirical and behavior-oriented studies that directly link financial literacy to banking product usage, especially in the context of digital finance, to support sustainable financial inclusion.Novelty: This study provides the first bibliometric mapping of the intellectual structure of financial literacy research in the Nepalese banking context, identifying evolution, core themes, and critical research gaps.